Ecological informations on Coprophanaeus (Coprophanaeus) gamezi Arnaud (Coleoptera: Scarabaeidae: Phanaeini) in a rural agricultural area in the depression of Maracaibo, Zulia State, Venezuela - Gámez, Jorge; Acconcia, Raffaele (Instituto de Ecología, A.C., 2009)
This paper reports the results of fields studies on the biology of Coprophanaeus (C.) gamezi Arnaud conducted in induced pastureland and banana plantations in the Lake Maracaibo Depression of the state of Zulia, Venezuela. Carrion – baited pitfall traps were used to monitor annual and daily activity cycles. Greatest abundance was observed in the banana plantations. Daily activity cycle was crepuscular and bimodal with approximately 30 min periods of activity at dusk and dawn. Daily rhythm was marked by a preference for low light intensities (0 – 30 Lux sunset, 0 – 3 Lux sunrise), higher humidities (87.6% – 89% sunset; 95.3% – 96.7% sunrise), and temperatures between 27.3ºC and 27.7 °C sunset and 24.9ºC and 25.1 °C sunrise. Most (73%) of the captured specimens were collected at sunset, perhaps as a consequence of interactions between an endogenous rhythm and certain environmental variables, especially temperature and light intensity. Coprophanaeus gamezi is one of the most important necrophages in open and semi open habitats studied where rainforest has been cut in the Maracaibo Depression